2017
DOI: 10.1038/srep42592
|View full text |Cite
|
Sign up to set email alerts
|

A combination of mutational and computational scanning guides the design of an artificial ligand-binding controlled lipase

Abstract: Allostery, i.e. the control of enzyme activity by a small molecule at a location distant from the enzyme’s active site, represents a mechanism essential for sustaining life. The rational design of allostery is a non-trivial task but can be achieved by fusion of a sensory domain, which responds to environmental stimuli with a change in its structure. Hereby, the site of domain fusion is difficult to predict. We here explore the possibility to rationally engineer allostery into the naturally not allosterically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…Moreover, when they form crystallographic dimers, these interfaces are highly different from the CA lipase dimer (Figs. 1B, 2) (30)(31)(32)(33). The dimeric state of CA lipase contributes solubility and stability.…”
Section: Ca Lipase Dimer Shows Core and Lid Domainmentioning
confidence: 99%
“…Moreover, when they form crystallographic dimers, these interfaces are highly different from the CA lipase dimer (Figs. 1B, 2) (30)(31)(32)(33). The dimeric state of CA lipase contributes solubility and stability.…”
Section: Ca Lipase Dimer Shows Core and Lid Domainmentioning
confidence: 99%
“…While specificity prediction requires both positive design (i.e., stabilization of the desired complex) and negative design (i.e., destabilization of unwanted complexes), affinity prediction considers only positive design [ 10 , 20 ]. For instance, computationally saturated mutagenesis and similar classical approaches focus chiefly on single targets (namely, stabilization of the desired complex) and only allow for testing the effects of single mutations [ 1 , 3 , 9 , 21 , 22 ]. Predicting specificity by these methods is, therefore, time-consuming and laborious, as separate computations are required for all possible targets.…”
Section: Introductionmentioning
confidence: 99%
“…At 30% sequences identity, only 22 unique presentative structures (Bacteria: 12; Eukaryota: 9; and Archaea: 1) of lipase have been found. In recent years, structural information and computational molecular modeling studies demonstrated their mechanistic properties [5,6]. The 3D structure of lipases usually have a common α/β hydrolase fold topology with mostly parallel β-sheets, flanked on both sides by α-helices [7].…”
mentioning
confidence: 99%